Comparative Study of FNAC and Histopathology in Diagnosis of Thyroid Swelling - Sharma, Bibek; Baral, Alina; Pokharel, Apar; Subedi, Deepak Jung (Journal of College of Medical Sciences-Nepal, 2023)
Introduction Fine Needle Aspiration Cytology (FNAC) is important for pre-operative and pre-treatment diagnosis of benign and malignant thyroid lesions, thus decreasing the incidence of unwanted surgeries. The objective of this research is to compare the FNAC and Histopathological findings of thyroid swelling. Methods The present study is a cross sectional study conducted on 30 patients in the Department of Otorhinolaryngology Head and Neck Surgery, College of Medical Sciences, Bharatpur, Nepal from January 2022 to December 2022. Thyroid swelling presented to OPD were examined clinically after thorough history taking and admitted to indoor and subsequently underwent surgery were included in this study. After Histopathology they were compared with preoperative FNAC report. In all cases, informed consent was taken prior to the surgery. Results FNAC shows thirteen (28.57%) non neoplastic and twenty-two (71.43%) neoplastic. Among non neoplastic thyroid swelling, colloid goiter was common. Among neoplastic thyroid swelling Papillary carcinoma was the most common. Cyto-histopathological correlation of 35 cases was done. Out of thirty-five cases fifteen (42.87%) were non neoplastic and twenty (57.15%) were neoplastic. Colloid goiter was most common. Sensitivity of our study was 88.24%, Specificity was 55.56 % and accuracy was 71.43%. Conclusions FNAC is a quick, safe, and reliable first-line diagnostic test for thyroid nodules. However, histopathology is the gold standard for the diagnosis of thyroid cancer and provides detailed information on the tumor size, location, and histological type.